2003
DOI: 10.1029/2001jd001225
|View full text |Cite
|
Sign up to set email alerts
|

An algorithm for retrieval of cloud microphysics using 95‐GHz cloud radar and lidar

Abstract: [1] We develop a new forward algorithm for the retrieval of effective size and ice water content (IWC) of ice crystals in clouds by using collocated 95-GHz (3.16 mm) cloud radar and lidar with the wavelength of 0.532 mm. Use of radar or lidar alone has a fundamental difficulty to obtain cloud microphysics because of the wide variety of size distributions of cloud particles, though it is effective to obtain cloud macrophysical information such as cloud boundaries. The combined use of radar and lidar can overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 40 publications
2
110
0
Order By: Relevance
“…Benedetti et al, 2003;Austin et al, 2009), radar-lidar (e.g. Donovan andvan Lammeren, 2001;Wang and Sassen, 2002;Okamoto et al, 2003;Hogan, 2008, 2010) and radar Doppler based techniques (e.g. Matrosov et al, 2002;Mace et al, 2002;Delanoë et al, 2007;Szyrmer et al, 2012).…”
Section: Cirrus and Mid-level Ice Cloudsmentioning
confidence: 99%
“…Benedetti et al, 2003;Austin et al, 2009), radar-lidar (e.g. Donovan andvan Lammeren, 2001;Wang and Sassen, 2002;Okamoto et al, 2003;Hogan, 2008, 2010) and radar Doppler based techniques (e.g. Matrosov et al, 2002;Mace et al, 2002;Delanoë et al, 2007;Szyrmer et al, 2012).…”
Section: Cirrus and Mid-level Ice Cloudsmentioning
confidence: 99%
“…Among them, the use of split window is effective to detect long-lasting cirrus clouds from geostationary satellite data, since no visible data are required. Lidar observation is also considered a powerful tool to detect cirrus clouds and to retrieve the optical properties of cirrus clouds [e.g., Platt, 1979;Sassen et al, 1990;Mace et al, 1998a;Okamoto et al, 2003]. With the launch of the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CA-LIPSO) and CloudSat, we now have a significant amount of new-generation observations for the vertical structure of cloud and aerosol from space.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several algorithms that utilize ground-based and space-based active remote sensing have been proposed for the retrieval of ice cloud microphysical properties. Most of the proposed algorithms can be classified in radar-only [e.g., Benedetti et al, 2003;Austin et al, 2009], radar-lidar [e.g., Donovan and van Lammeren, 2001;Wang and Sassen, 2002;Okamoto et al, 2003;Delanoё andHogan, 2008, 2010] and radar -Doppler based techniques [e.g., Matrosov et al, 2002;Mace et al, 2002;Delanoё et al, 2007], or both lidar and multiparameter radar [Sato et al, 2009]. Extensive reviews on existing algorithms and their performance can be found in Heymsfield et al [2008], Protat et al [2010] and Stein et al [2011].…”
Section: Introductionmentioning
confidence: 99%